2018
DOI: 10.1002/anie.201712662
|View full text |Cite
|
Sign up to set email alerts
|

Design of Metal‐Free Polymer Carbon Dots: A New Class of Room‐Temperature Phosphorescent Materials

Abstract: Polymer carbon dots (PCDs) are proposed as a new class of room-temperature phosphorescence (RTP) materials. The abundant energy levels in PCDs increase the probability of intersystem crossing (ISC) and their covalently crosslinked framework structures greatly suppress the nonradiative transitions. The efficient methods allow the manufacture of PCDs with unique RTP properties in air without additional metal complexation or complicated matrix composition. They thus provide a route towards the rational design of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
366
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 473 publications
(389 citation statements)
references
References 48 publications
10
366
0
2
Order By: Relevance
“…Meanwhile, excitation‐dependent fluorescence emission was observed when Gly‐CDs were excited with different wavelengths from 300 to 410 nm(Figure 1e), due to the normal size distribution of Gly‐CDs 50. The UV–vis absorption spectrum and fluorescence spectrum are all consistent with CDs reported before 49,51. Figure 1f shows the Gly‐CDs functional groups measured by the Fourier transform infrared spectroscopy (FT‐IR).…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, excitation‐dependent fluorescence emission was observed when Gly‐CDs were excited with different wavelengths from 300 to 410 nm(Figure 1e), due to the normal size distribution of Gly‐CDs 50. The UV–vis absorption spectrum and fluorescence spectrum are all consistent with CDs reported before 49,51. Figure 1f shows the Gly‐CDs functional groups measured by the Fourier transform infrared spectroscopy (FT‐IR).…”
Section: Resultsmentioning
confidence: 99%
“…Herein we use sodium alginate, a biopolymer obtained from brown seaweed, along with ethylenediamine to prepare carbon dots via a hydrothermal method. The synthetic details were reported previously . Figure shows a TEM image of the CDs synthesized.…”
Section: Figurementioning
confidence: 99%
“…The broad bands at 3000–3500 cm −1 were assigned to stretching vibrations of amino (NH 2 ) and hydroxy (OH) groups. The peaks at 1150, 1450, and 1610 cm −1 also related to the CO and OH bonds, indicating there were oxygen‐rich properties of both N‐CNRs, and the peak at ≈1750 was attributed to the CO bond . Therefore, it can be concluded that the functional groups improved the hydrophilicity of the N‐CNRs in an aqueous solution system, which was expected to render the N‐CNRs with an excellent water solubility characteristic.…”
Section: Comparison Between Three Types Of Previously Studied Carbon mentioning
confidence: 92%